Citizen Activities in Energy Transition User Innovation, New Communities, and the Shaping of a Sustainable Future - Hyysalo, Sampsa (Routledge Studies in Innovation, Organizations and Technology, 2021)
This book addresses the rapidly changing citizen roles in innovation, technology adoption, intermediation, market creation, and legitimacy building for low-carbon solutions. It links research in innovation studies, sustainability transitions, and science and technology studies, and builds a new approach for the study of user contributions to innovation and sociotechnical change. Citizen Activities in Energy Transition gives detailed and empirically grounded overall appraisal of citizens' active technological engagement in the current energy transition, in an era when Internet connectivity has given rise to important new forms of citizen communities and interactions. It elaborates a new way to study users in sociotechnical change through long-term ethnographic and historical research and reports its deployment in a major, decade-long line of investigation on user activities in small-scale renewables, addressing user contributions from the early years to the late proliferation stages of small-scale renewable energy technologies (S-RETs). It offers a much-needed empirical and theoretical understanding of the dynamics of the activities in which users are engaged over the course of sociotechnical change, including innovation, adoption, adjustment, intermediation, community building, digital communities, market creation, and legitimacy creation. This work is a must-read for those seeking to understand the role of users in innovation, energy systems change and the significance of new digital communities in present and future sociotechnical change. Academics, policymakers, and managers are given a new resource to understand the "demand side" of sociotechnical change beyond the patterns of investment, adoption, and social acceptance that have traditionally occupied their attention.